Factors Associated with Vaginal Infections in Pregnant Women with Preterm Labor at the Government Hospital - Rasri, Pornuma; Maksakul, Pimjai (Journal of The Royal Thai Army Nurses, 2025)
This retrospective analytical study aimed to investigate the prevalence and associated factors of vaginal infection among pregnant women with preterm labor. The study sample comprised 327 pregnant women who were admitted to a hospital. Data were collected from medical records using a structured data collection form and analyzed with descriptive statistics and the chi-square test. The findings revealed that the prevalence of vaginal infection in pregnant women with preterm labor was 42.8%. Statistically significant factors associated with vaginal infection included substance use ( = 6.782, p = .014) and body mass index ( = 6.920, p = .048). In contrast, other general characteristics such as age, educational level, and occupation were not significantly associated. These findings highlight the need for early screening of pregnant women with such risk factors during antenatal care, as well as the development of policies and nursing guidelines focusing on health promotion, substance use reduction, and nutritional management to prevent vaginal infections and reduce the risk of preterm birth.